Religious Moderation in Islamic Education in Indonesia - Ahmad Syaikhu; Mochamad Syaifudin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
The Quran is the holy book of Muslims whose contents are very suitable for all times and places (maslahah li kulli zaman wa makan), one of the interesting concepts in the Quran is about religious moderation. Religious moderation is a theory that contains the ideas of peace, justice, and moderation in all aspects of life in this world. Be it moderate in Aqidah, Worship, Muamalah/taqwa, and moderate in Tashri' (upholding Syari’at). While the term religious moderation always described in the Quran with various personality types, including honest, open, love, and flexible, mutually united, universal and universal, all of which are inseparable, mutually reinforcing and beneficial. Religious moderation is also emphasized in Islamic education in Indonesia, especially in terms of learning techniques and material content including elements of Quran Hadith, Fiqh, Aqidah Akhlaq, Syari’at (Islamic law) and Islamic Tarikh (Islamic history). All Islamic education materials above are presented in a manner and use techniques that prioritize the values and principles of religious moderation to foster a flexible, compassionate, and caring character and personality in a fair and equal manner. In facing the problems that come one after another, the more plural generations who uphold the principle of equality and mutual respect for the principle of difference, the generation that loves religious diversity will emerge to make Indonesia a tolerant nation.